The higher power of Lucky - Patron, Susan; Phelan, Matt (New York : Atheneum Books for Young Readers, 2006)
Fearing that her legal guardian plans to abandon her to return to France, ten-year-old aspiring scientist Lucky Trimble determines to run away while also continuing to seek the Higher Power that will bring stability to her life.
"A Richard Jackson book."
1010/b Lexile
Newbery Medal, 2007
Keywords: Abandoned children -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Runaway children -- Juvenile fiction